Blind symbol-rate estimation for short and bursty communications - Yang, Chaosan (2022)
The design of a blind receiver for unsynchronized bursty communications is a challenging task, especially when the data burst duration is very short and the over-sampling ratio (OSR) at the receiver is a non-integer value. In this article, the problem of blind symbol-rate estimation for bursty communications is studied. A cyclostationary method with bias removal (CS-BR) is proposed to improve the accuracy of the 'OSR peak' detection in cyclostationary method when the length of signal burst is very short. Factors which affect the accuracy of the proposed blind symbol-rate estimation are thoroughly analyzed. Both field measurement data simulations and Monte Carlo simulations show that by using our proposed CS-BR method, the accuracy of blind symbol-rate estimation can be significantly improved, and the root-mean-square-error of the estimated OSR can be reduced to as small as 10-4 even if each short data burst consists of only tens of symbols.